Study of Effect of Lactobacillus gasseri Filtrate on Growth of Some Pathogenic Fungi - AI-Marjani, l. F.; Abbod, z. H.; Abdalkarim, M.K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The inhibitory effect concentrated filtrate of local Lactobaciilusgasseri against Candida albicans and Trichophyton mentagrophytes, T  ruhrum  and Aspergillus  flavus which were isolated from infected cases  in human  beings, tested  using two methods  :well diffu  ion andMixed with the mold medium (Sabouraud agar).The  results  showed  that the concentrated filtrate  of L. gasseri haveinhibitory effect against Cundida ulbicans, the inhibition  zone was 13 mm. As well  as, the concentrated  tiltrate inhibited, considerably Trichophyton   mentagrophytes,   T. rubrum   and   Aspergillus   jlavus growth   when  the  filtrate   was  mixed   with  Sabouraud   agar,  the inhibition activity was (57.6 , 41.2 , 66.6 )%  against Trichophyton mentagrophytes, T.rubrum andAspergillusflavu.'i respectively.Results  showed  that concentrated filtrate of L.gasseri showed  strong activity  against  T. mentagrophytest spores gcrminatio!l  (the inhibition was 79.45%) by Mixing Lhfiltrate with the mold medium (Sabouraud agar).